Problems of Religious Guidance and Counseling Teachers in Overcoming Student Delinquency at SMA Negeri 1 Popayato, Pohuwato Regency - Hasan, Mantik; Mobonggi, Arten H. (Pascasarjana IAIN Sultan Amai Gorontalo, 2025)
Delinquency is deviant behavior that disturbs the peace of others and oneself. Student delinquency is an expression of anxiety, worry, or mental pressure felt by students as a response to the influence of the surrounding environment. This study uses qualitative methods with descriptive methods. Qualitative research is to make it easier to find out about juvenile delinquency in SMA Negeri 1 Popayato. Data collection techniques in this study are interviews and observation techniques. The sources of informants in the study were the Principal, Guidance and Counseling Teachers, and Students. The results of the study showed the problems of religious guidance and counseling teachers in overcoming student delinquency that occurred in SMA Negeri 1 Popayato, Pohuwato Regency, which can be seen from several stages that have been carried out by the school, in this case, the Principal, vice principal, and guidance and counseling teachers. First, the mental attitude of adolescents should be strengthened so that they can face and solve their problems. In addition, it is essential to provide education that is not only limited to increasing knowledge and skills, but also includes mental education, personality formation, religious values, and morals. Next, adequate facilities should be provided, and an atmosphere should be created for the healthy development of adolescent personalities. In addition, discussion groups should be organized to provide opportunities for adolescents to express their views and opinions while providing positive direction. Finally, establish a training place that can be used to channel adolescent creativity, both for those involved in delinquent behavior and those who are not.